Tanggung Jawab Hukum Badan Pertanahan Nasional Terkait Ketidaksesuaian Hasil Pengecekan Sertifikat Secara Elektronik - Sumardani, Ni Made Rian Ayu; Bagiastra, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 02 (2021), 2021)
Abstract The aim of this paper are to discover the regulation of electronically checked documents and to examine the legal responsibility of the Indonesian National Land Office based on the Regulation the Minister of Agrarian 5/2017 . The research method applies a normative legal research. Results indicated that electronically checked documents, which examine based on the regulation stated in Article 1 paragraph 2 letter a of the Regulation the Minister of Agrarian 5/2017 which is where electronic certificate checking will replace manual certificate checking as regulated in the Regulation of the Head of the National Land Agency 8/ 2012. Legal responsibility related about errors in the results of checking certificates electronically is the responsibility of BPN in accordance with Article 10 paragraph (4) and paragraph (5) of the Regulation the Minister of Agrarian 5/2017 with legal responsibility in the form of clarification explanation and improvement of the database system . Abstrak Tulisan ini memiliki tujuan untuk mengetahui pengaturan pengecekan sertifikat secara elektronik dan mengkaji tanggung jawab Badan Pertanahan Nasional terkait ketidaksesuaian hasil pengecekan sertifikat dalam Permen Agraria 5/2017.  Penelitian ini menggunakan metode penelitian hukum normatif. Hasil penelitian menunjukkan bahwa, pengaturan pengecekan sertifikat secara elektronik diatur pada pasal 2 ayat (2) huruf a Permen Agraria 5/2017 , yang dimana pengecekan sertifikat secara elektronik akan menggantikan pengecekan sertifikat secara manual yang diatur pada   Perkaban No. 8/2012 . Tanggung jawab hukum terkait adanya kesalahan pada hasil pengecekan sertifikat secara elektronik merupakan tanggung jawab dari pihak BPN sesuai dengan Pasal 10 ayat (4) dan ayat (5) Permen Agraria 5/2017 dengan tanggung jawab hukum berupa klarifikasi penjelasan dan perbaikan pada sistem pangkalan data .